2018
DOI: 10.17221/149/2017-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Associations between polymorphisms in the myostatin, α<sup>A</sup>-globin and lactate dehydrogenase B genes and racing performance in homing pigeons

Abstract: The aim of this study was to investigate the associations between variability in the myostatin, α<sup>A</sup>-globin and lactate dehydrogenase B genes and racing performance in homing pigeons. The study included 123 animals (60 females and 63 males) participating in racing competitions. The data set used in this study consisted of scores from 17 short (≤ 400 km) and 11 long races (≥ 500 km) (2589 race records in total). Our study is the first study to analyse the associations between polymorphisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…The LF-A1 factor occurring in TT individuals may effect on the expression of the pigeon α A -globin gene, however, there is no evidence at the current stage of research. Recently, a very low frequency of allele T (0.077) and only CT genotype detected (no TT individuals) in the group of homing pigeons was reported [Dybus et al 2018].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The LF-A1 factor occurring in TT individuals may effect on the expression of the pigeon α A -globin gene, however, there is no evidence at the current stage of research. Recently, a very low frequency of allele T (0.077) and only CT genotype detected (no TT individuals) in the group of homing pigeons was reported [Dybus et al 2018].…”
Section: Resultsmentioning
confidence: 99%
“…There are many tools for selection, but the most common types of markers in genomes are SNPs [Goldstein andCavalleri 2005, Jacob et al 2018], nowadays, genetic markers have been used to predict racing perform-ance in pigeons [Proskura et al 2014, Proskura et al 2015, Proskura et al 2017, Ramadan et al 2018, Dybus et al 2018. Recently, in whole-genome study, the CASK gene was marked as an important genetic factor for fast flight, long endurance, and accurate navigation was revealed [Gazda et al 2018].…”
Section: Introductionmentioning
confidence: 99%
“…With the growing popularity of pigeon racing as a lucrative sport, molecular approaches to the identification of genetic markers, such as SNPs, important to racing and homing phenotypes have been explored in the past [ 1 , 2 , 3 , 5 , 6 , 7 , 8 , 12 , 13 , 17 , 26 , 42 ]. The results of this study demonstrated the application of KASP as a method to detect SNPs previously identified to be associated with the racing traits of pigeons.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, higher overall capacity in terms of endurance and recovery, or speed, velocity, and stress resistance are preferred traits [ 2 , 3 , 6 , 8 , 9 , 10 , 11 ]. Besides health management programs, including the appropriate choice of feeds, medical supplements, and physical conditioning regimens to improve pigeons’ performance in competitions, the identification of genetic markers for valuable traits associated with racing performance has also been reported and explored towards expediting success in selective breeding [ 1 , 6 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. The determination of single nucleotide polymorphisms (SNPs) that seem to cause phenotypic differences is one of the most commonly used approaches to identify potentially essential genetic markers [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are many factors affecting these traits [21], so searching for the appropriate genetic markers is crucial for this purpose. The most common types of markers in genomes are SNPs [22,23], and some of them have been used to predict racing performance in pigeons [20,21,[24][25][26].…”
Section: Short Communicationsmentioning
confidence: 99%